PEDAGOGICAL SIGNIFICANCE OF TEACHING ACTION-SEMED LEXEMAS TO CHILDREN OF EARLY SCHOOL AGE - Ne'matova Mahfuza Ma'rufjon kizi (Bright Mind Publishing, 2025)
This article discusses the pedagogical significance of teaching action-semed lexemes to children of early school age and its role in child psychology, as well as what methods and techniques are appropriate for teaching them to primary school students.
Keywords: Lexemes with action sema, sema, interactive methods, verbs of action and state, transitivity.